Sinergitas Jejaring Klaster MEP Sekarbela dalam Kerangka Sistem Inovasi Daerah - Sri Apriani Puji Lestari; Agus Kurniawan; Rasyid Ridha (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Industrial cluster is one of the approaches used as an effort to develop economic activities within the framework of regional innovation systems. The cluster approach is expected to be able to stimulate innovation through sharing of information, experience and knowledge between actors, and encouraging increased linkages of expertise in cluster networks. This study aims to identify stakeholders involved and the extent of stakeholder relations in the Sekarbela pearl, gold and silver (MEP) industry cluster network within the framework of regional innovation systems. This study usedsurvey method with qualitative and quantitative descriptive approaches on secondary and primary data. Analysis conducted were descriptive qualitative analysis and social network analysis. Results shows that actors involved in the network cluster consisted of various elements, such as the central and local governments, private sector, financing institutions, academicians, and associations. Based on the measurement of betweenness centrality and closeness centrality, the Department of Industry, Cooperatives and SMEs of Mataram City, Local Development Planning Agency (Bappeda) of Mataram City, Mataram City Trade Office, NTB Province Cooperative and MSME Office, and the Ministry of Industry are liaison actors in a network chain that facilitates the dissemination of information in the network, as well as the ease and proximity to communicate with each other. The role of academics and funding institution inadequate and this affects the development of cluster innovation. More active role is required from various parties involved, as well as knowledge transfer and information sharing between actors in the cluster network, in order to create innovative and competitive products.